2018
DOI: 10.1242/jcs.209932
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screening identifies a mechanosensitive ROCK-JAK2-STAT3 network central to myofibroblast activation

Abstract: Myofibroblasts play key roles in wound healing and pathological fibrosis. Here, we used an RNAi screen to characterize myofibroblast regulatory genes, using a high-content imaging approach to quantify α-smooth muscle actin stress fibers in cultured human fibroblasts. Screen hits were validated on physiological compliance hydrogels, and selected hits tested in primary fibroblasts from patients with idiopathic pulmonary fibrosis. Our RNAi screen led to the identification of STAT3 as an essential mediator of myof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 76 publications
3
23
0
Order By: Relevance
“…4A). Many of these genes are strongly linked to myofibroblast activation and fibrotic tissue remodeling (Bhattacharyya et al, 2016;Estany et al, 2014;Henderson and Sheppard, 2013;Hung et al, 2013;Le et al, 2014;Oh et al, 2018;Schafer et al, 2017;Trojanowska, 2008;Tschumperlin et al, 2018), consistent with our prior functional assays demonstrating that pracinostat reduces pro-fibrotic cellular functions. GO analysis using DAVIDv6.8 revealed that pracinostat blocked the TGFβ induction of pro-fibrotic pathways, such as wound healing, positive regulation of MAPK cascade and ECM organization ( Fig.…”
Section: Hdac Inhibition Blocks Gene Expression Changes Associated Wisupporting
confidence: 85%
See 2 more Smart Citations
“…4A). Many of these genes are strongly linked to myofibroblast activation and fibrotic tissue remodeling (Bhattacharyya et al, 2016;Estany et al, 2014;Henderson and Sheppard, 2013;Hung et al, 2013;Le et al, 2014;Oh et al, 2018;Schafer et al, 2017;Trojanowska, 2008;Tschumperlin et al, 2018), consistent with our prior functional assays demonstrating that pracinostat reduces pro-fibrotic cellular functions. GO analysis using DAVIDv6.8 revealed that pracinostat blocked the TGFβ induction of pro-fibrotic pathways, such as wound healing, positive regulation of MAPK cascade and ECM organization ( Fig.…”
Section: Hdac Inhibition Blocks Gene Expression Changes Associated Wisupporting
confidence: 85%
“…Specifically, diseased lung fibroblasts have been shown to exhibit causative alterations in DNA methylation, histone acetylation and micro (mi)RNAs when compared to their non-diseased counterparts (Coward et al, 2018(Coward et al, , 2014(Coward et al, , 2009Huang et al, 2014;Khalil et al, 2015;Lino Cardenas et al, 2013;Liu et al, 2010;Miao et al, 2018;Sanders et al, 2012Sanders et al, , 2017Tang et al, 2013;Xiao et al, 2016;Yang et al, 2014Yang et al, , 2013. Recently, we identified several epigenetic regulators in an siRNA screen of fibroblast activation (Oh et al, 2018). Taken together, these studies demonstrate that fibroblast activation is a complex phenomenon regulated by multiple epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with this hypothesis, Sigmar1 upregulation was reported upon cell treatment with other ER stress inducers, such as glucose, heat shock, and thapsigargin (72). Also, previous genetic screenings identified either the noncanonical TGF-β pathway or calcium as a major regulator of myofibroblast activation (23)(24)(25). For instance, TRPC6-mediated calcium signaling induced myofibroblast differentiation, although this channel essentially controls calcium influx from the extracellular space and not its release from the ER, as in our model (24).…”
Section: Discussionsupporting
confidence: 54%
“…Genetic screening has been used over the last several years to discover relevant pathways involved in myofibroblast activation (23)(24)(25). Here, we report the results of a high-content (HC), fluorescence-microscopy-based high-throughput screening (HTS), that led to the discovery of haloperidol, a common antipsychotic drug, as a potent inhibitor of myofibroblast activation.…”
Section: Introductionmentioning
confidence: 99%